Gastric Cancer: Past, Present and Future - Annie On-On Chan; Benjamin Chun-Yu Wong; Shiu-Kum Lam (Canadian Journal of Gastroenterology)
Gastric cancer remains a major cause of cancer mortality in the world. However, in the past 10 decades, the view of gastric cancer has been changing. This includes the unexplained decline in the incidence of the cancer, the proximal shift of the cancer in the stomach, the identification of Helicobacter pylori as an etiological agent, rapid development in molecular tumour biology, new treatment modalities and the adoption of mass screening for prevention. This article reviews the changing views of gastric cancer and the latest developments.